The Evaluation of the Merdeka Curriculum in Enhancing Student Learning Independence in the Digital Era - Afifah Naurah Deliana; Amrina Rosyada; Ekis Sagita (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The Ministry of Education, Culture, Research, and Technology of the Republic of Indonesia developed the Merdeka Curriculum with the aim of enhancing students' learning independence amidst the rapid technological advancements in the digital era. The objective of this research is to determine the effectiveness of the Merdeka Curriculum in improving students' learning independence. This study employs a qualitative approach, utilizing interviews, observations, and documentation studies in several schools that have implemented this curriculum. The findings show that although the Merdeka Curriculum provides students with the freedom to choose how they want to learn, factors such as digital infrastructure do not support this effectively.